LITERARY TRANSLATION AND ITS STYLISTIC ANALYSIS - Inog’omjonova Robiya Rustamjon qizi (Journals Park Publishing, 2024)
Unlike painters, sculptors, or composers in the fields of fine arts and music, writers express their inner world and their perception of reality through unique means that may not be universally understood. Just as a painter utilizes visual imagery and a musician uses auditory imagery, a translator must possess a high level of skill to recreate and represent these elements through verbal imagery. In literary translation, the aesthetic qualities stem from the intricate restructuring of the artistic image found in the original text. These are tools specific to the language in which the writer crafts their literary work.[1]
Keywords: translation, literary translation, stylistics, translation, language features.